Equações antropométricas para estimativa da massa muscular esquelética apendicular de idosas - Pereira, Piettra Moura Galvão (2012)
Sarcopenia is presented as a risk factor for onset of disease, functional disability and mortality from all causes. To contribute towards a better understanding of this problem, this dissertation is presented in two articles. First it is a narrative review with the description of methods of measurement of skeletal muscle mass, considering the discussions about changes in the components of the body related to aging. The second article, besides discussing the cross-validation of two anthropometric equations: Baumgartner et al. and Tanko et al. commonly used to estimate appendicular muscle mass, was devoted to the development and cross validation of anthropometric equations for estimation of appendicular muscle mass in elderly women. In summary, the collection of articles presented here can be seen that there are different methods and techniques available for measuring total or appendicular MME in the elderly, the choice between them depends on the cost, availability, convenience, accuracy and sensitivity to identify the changes that occur during the aging process. As regards cross-validation of equations Baumgartner et al. (2002) and Tanko et al. (1998), both not shown to be valid for use in older women with similar characteristics to our sample. In the present study ten anthropometric equations were developed with the aid of multiple linear regression analyzes, among these three equations met all criteria for cross-validation using MMADXA as the dependent variable and can be used interchangeably according to the convenience of those involved in research or clinical applications.